Effect of kelor (Moringa oleifera Lam) ethanolic leaves extract on uterus of pregnant mice and its teratogenicity - Desy Armalina; Neni Susilaningsih; Indah Saraswati; Eva Annisa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Moringa oleifera Lam (Moringaceae) is a source of additional dietary. It contains 9 essential amino acids, calcium, iron, potassium, magnesium, zinc and vitamins A, C, E and B which have a major role in the immune system. Previous study reported that M. oleifera Lam can increase the hemoglobin of breastfeeding mothers. In contrast, M. oleifera Lam is well known as abortifacient plant, therefore it is not recommended to use during pregnancy. The aim of this study was to evaluate the effect of M. oleifera Lam ethanolic leaves extract M. oleifera Lam on uterus of pregnant mice and its teratogenic effect. Twenty pregnant female Balb/c mice were used in this experimental study. Mice were randomized divided into four groups with five mice in each group. Group C as control, mice were not given anything. Group T1-T3 were given M. oleifera Lam ethanolic leaves extract during pregnancy age 7-18 days with doses of 10, 20 and 30 mg/kg BW, respectively.  Phytochemical analysis was performed quantitatively and qualitatively. On day 19, a caesarean section was performed to take the uterus, count the number of living foetus, dead foetus, disability, and other morphological abnormalities. No significant difference between all groups was observed. The abortifacient effect was not also observed in the uterus. Qualitative phytochemical analysis results showed that alkaloids, flavonoids, phenols, steroids, and tannins are identified in this extract. Quantitative steroids analysis results showed that the extract contained steroids of 1057.6 ppm. In conclusion, the M. oleifera Lam ethanolic leaves extract at dose of 30 mg/kg BW does not show any effect on the uterus of pregnant mice. Further study concerning the effects on other organs and hormones is recommended.